An Ecolinguistics Perspectives For English Syllabus Development - Nur Endah Tjendani; I Made Suastra; Aron Meko Mbete; Ni Luh Nyoman Seri Malini (e-Journal of Linguistics, 2019)
This current study was intended to develop the ecolinguistic perspective-basedsyllabus. The descriptive qualitative method was applied and natural phenomena were used todevelop syllabus. The phenomena focused on to what extent English was mastered by learnersand what learning and teaching strategies were applied. The data were obtained through test,questionnaire and direct observation for the need analysis. The State Document related to thecurriculum policy was referred to in the situation analysis. The syllabus was developed based onthe results of the need analysis and situation analysis and the ecolinguistic perpective-relatedtheories. The contents of the syllabus were developed based on the following elements; they aretext, context, linguistic elements, learning situation, teaching and learning activities (KegiatanBelajar Mengajar, abbreviated to KBM) and evaluation. The content of the text was adjusted tothe transactional and interpersonal functions. The context was created based on the inter-, intra-,and trans-cultural contexts of the ecological, social and ideological dimensions. KBM wasprepared in accordance with the cognitive linguistic process for the language-related activitiesand based on the situation chosen by learners for the language production. The outcome oflanguage performance was measured using the performance assessment system, causing thecontents of the syllabus to reflect that one element was connected with another in such a way thatthey formed one integral language meaning.